The Application of Stem Cells from Different Tissues to Cartilage Repair - James N. Fisher; Irene Tessaro; Tommaso Bertocco; Giuseppe M. Peretti; Laura Mangiavini (Hindawi Limited, 2017)
The degeneration of articular cartilage represents an ongoing challenge at the clinical and basic level. Tissue engineering and regenerative medicine using stem/progenitor cells have emerged as valid alternatives to classical reparative techniques. This review offers a brief introduction and overview of the field, highlighting a number of tissue sources for stem/progenitor cell populations. Emphasis is given to recent developments in both clinical and basic sciences. The relative strengths and weaknesses of each tissue type are discussed.